Antioxidant and Antimicrobial Activity of Different Plant Parts of Garcinia prainiana- an Endangered Plant - Selvi Asang, Gogula; Nasrah Mohd Khairuddin, Nur; Alias, Nadiawati; Ahmad, Aryati; Rohani Wan Taib, Wan (International Journal of Engineering and Technology, 2018)
Garcinia prainiana is a critically endangered tree belongs to the family Clusiaceae found native in Asia and yet not many studies have been conducted to scientifically study its medicinal potential. The present study was conducted to evaluate potential antioxidant, antimicrobial and to screen the phytochemical screening of Garcinia prainiana methanolic extract. The solvent used for extraction was methanol for dried leaves, twig and fruit sample. Antioxidant activity was tested using free radical diphenylpicrylhydrayl (DPPH) assay. While for antimicrobial activity, the disc diffusion method was carried out against six types of pathogenic bacteria from Gram-positive and Gram-negative bacteria. In addition, quantitative phytochemical screening was carried out to determine total phenolic and flavonoid content of the methanolic extract. The plant showed moderate antioxidant activity. Garcinia leaves extract showed the highest antioxidant activity (70.43%) followed by twig extract (47.46%) and fruit extract (44.45%). The IC50 value managed to be obtained from leaves extract at 0.26 mg/ml. Meanwhile, for antimicrobial activities, zone of inhibition was determined at 100 mg/ml for leaves extract (9 Â± 0.73 mm) and twig extract (7 Â±0.5 mm) against Salmonella typhimurium ATCC 14028. Quantitative phytochemical screening showed that total phenolic content was the highest in leaves extract at 51.83mg GAE/g, while for total flavonoid content, fruit extract showed the highest value at 80.93 mg QE/g. Total phenolic content showed a good correlation with the antioxidant activity, but not with total flavonoid content.Â